Utilization of Voki Application as an Interactive Media to Improve Speaking Skill of Ninth Grade Students in Junior High School - Harahap, Nury Ana; Rahman Hz, Benni Ichsanda (Journal of English Language and Education, 2025)
This study aims the effectiveness of the Voki application as an interactive digital media tool to improve the speaking skills of ninth-grade students in a junior high school in Indonesia. Many students face psychological barriers such as anxiety, low confidence, and fear of making mistakes, which hinder their speaking performance in English. By integrating Voki an online platform that allows students to create speaking avatars into four speaking lessons, this study explored how the application influenced students' confidence, motivation, and participation. The research employed a qualitative case study design and involved 30 students who completed a questionnaire and 10 students who participated in in-depth interviews. The questionnaire data, analyzed using descriptive statistics, revealed that the majority of students had positive perceptions of Voki, reporting increased confidence, reduced anxiety, and improved pronunciation and fluency. Interview results supported these findings, highlighting that features such as voice recording, avatar customization, and audio playback encouraged independent learning and reduced fear of speaking. The findings align with Krashen’s Affective Filter Hypothesis and Mayer’s Cognitive Theory of Multimedia Learning, indicating that emotionally safe and multimodal environments foster better speaking performance. Overall, this study demonstrates that Voki is an effective, accessible, and engaging tool for enhancing speaking skills and offers practical implications for integrating digital tools into English language instruction.